The importance of pharmaceuticals from RDC No. 44 august 17 2009 in pharmacies and drugstores: an integrative review (Research, Society and Development, 2022)
Objective: To verify, from an integrative review, the role of the pharmacist after the implementation of Resolution 44/2009, the first ANVISA resolution that supported such activities in pharmacies and drugstores. Methodology: This is an integrative review to observe the importance of the pharmacist from RDC No. 44 August 17 2009, in pharmacies and/or drugstores in Brazil. The guiding question of this review was “Is the presence of the pharmacist necessary to comply with good pharmaceutical practices established by RDC No. 44 August 17 2009?”. The studies were selected from the Scientific Electronic, Library Online (SciELO), Google Scholar and Latin American and Caribbean Literature on Health Science (LILACS) databases, based on descriptors. Results: Of the 700 articles found in the databases selected for the study, only 12 were chosen after the inclusion criteria, which address pharmaceutical care, pharmaceutical services, rational use of medicines, reverse logistics, compliance with sanitary measures during prescriptions and good pharmaceutical practices. Conclusion: It is necessary to update RDC nº 44  August 17 2009 to include the new profile of the pharmacist in the conduct of clinical evaluation and/or monitoring of therapy within health facilities and the new concept of pharmacy, from 2014 onwards, with the objective of reducing the divergences between the wording of the regulations and the new roles of the professional and the establishment in relation to health care.